Principles for a pedagogy of unlearning. Issue 2 (3rd March 2020) - McLeod, Kim; Thakchoe, Sonam; Hunter, Mary Ann; Vincent, Kate; Baltra-Ulloa, Ann Joselynn; MacDonald, Abbey
ABSTRACT: In this article we make the case that 'unlearning' is an important dimension of professional reflective practice that can offer new insights when done collaboratively. We do so as an interdisciplinary group of academics interested in 'undoing' the conventional and individualising norms of reflective practice in academic settings, particularly when it comes to planning and reflecting on group processes for research. In the process of planning a project to investigate mentoring in the professions of social work and teaching, we reflected on our own collaborative academic practices through co-facilitated discussion, the creation of visual 'd/artaphacts', written reflections on our perceptions of 'unlearning' and academic collaboration, and reviewing how our diverse disciplines have engaged with unlearning in research literature and practice. These responses generated insights into the intricacies of the collaborative practice of unlearning in a professional research environment. We draw on these conversations, d/artaphacts, and reflections to compose five principles for a pedagogy of unlearning that can be applied in mentoring and professional practice settings. The principles highlight the importance of approaching unlearning as a collaborative activity for sustainable professional practice and for supporting the development of professional identities in fluid and complex relational work environments.